Impurity effects of the Λ hyperon in the hypernuclear systems Λ25Mg and Λ29Si. (17th September 2021) - Cui, Ji-Wei; Zhou, Xian-Rong
Abstract: Based on the beyond-mean-field Skyrme–Hartree–Fock model, impurity effects of the Λ hyperon in the hypernuclear systems Λ 25 Mg and Λ 29 Si are investigated, respectively. Four cases, in which the Λ hyperon occupies the single-particle orbitals Λ [000] 1 2 +, Λ [110] 1 2 −, Λ [101] 3 2 − and Λ [101] 1 2 −, are focused. In each case, the potential energy surface and the energy curves projected on certain angular momenta are employed to show the influence of the Λ hyperon on the nuclear core. Beside the shrinkage effect that is induced by the Λ hyperon occupying the s Λ orbital, it is found that the Λ hyperon on the p Λ orbital, Λ [110] 1 2 −, drives the nuclear core toward a prolate shape, while the ones on the other two p Λ orbitals, Λ [101] 3 2 − and Λ [101] 1 2 −, drive the nuclear core toward an oblate shape. The energy spectra and the corresponding intra-band E 2 transition rates for the rotational bands are given as a prediction for future experiments.